The Variation of Arabic Teaching Method at SMPIT Tahfidz Shohibul Qur’an Kampar - Khusniah, Hikmatul; Wahyudi, Hakmi; HIdayat, Nandang Sarip (Universitas Ahmad Dahlan, 2024)
This descriptive qualitative research aims to determine the method of teaching Arabic at SMPIT Tahfiz Shohibul Qur'an Kampar. Data collection from school principals and Arabic teachers used interview techniques, observation and documentation regarding Arabic teaching methods carried out at SMPIT Tahfiz Shohibul Qur'an Kampar. This research shows that there are several methods used in learning Arabic, including; 1) the method used is istima' and kitabah; 2) the method used in learning Arabic is using social media as a learning medium, and utilizing technology such as TV and others. The obstacle faced by the SMPIT Shohibul Qur'an school is the lack of adequate teachers in teaching Arabic, because of the lack of teachers in this field the competence to teach Arabic is reduced. So that only methods that already exist are used. The conclusion this research is 1) the method used is istima' and kitabah; 2) the method used in learning Arabic is using social media as a learning medium, and utilizing technology such as TV and others; 3) The obstacle faced by the SMPIT Shohibul Qur'an school is the lack of adequate teachers in teaching Arabic, because of the lack of teachers in this field the competence to teach Arabic is reduced. So that only methods that already exist are used.